2008
DOI: 10.1002/polb.21521
|View full text |Cite
|
Sign up to set email alerts
|

Thermal treatment of dense polyimide membranes

Abstract: A study has been conducted to clarify the relationship between polymer structure, annealing temperature, and the extent of plasticization by high‐pressure CO2 for two typical polyimide membranes; BTDA‐DAPI (poly(3,3′‐4,4′‐benzophenone tetracarboxylic–dianhydride diaminophenylindane) and 6FDA‐TMPDA (poly(2,2′‐bis(3,4′‐dicasrboxyphenyl) hexafluoropropane dianhydride–2,3,5,6‐tetramethyl‐1,4‐phenylenediamine). Both membrane materials are exposed to varying levels of thermal annealing at 200 and 250 °C. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 39 publications
5
52
0
Order By: Relevance
“…4 shows the results of the emission spectra for the 6FDA-mPDA, 6FDA-DAP, and 6FDA-DAR membranes. CTCs are typically formed between the nucleophilic fivemember rings and electrophilic six-member rings in polyimides [20,21,43]. The hydroxyl groups are likely to form hydrogen bonds, thereby tightening the polymer interchain structure to strengthen inter-chain CTCs, as evidenced by a previous study, which showed that hydroxyl moieties increased the intersegmental cohesive energy density (CED) in OH-functionalized polyimides [44].…”
Section: Physical Properties Of the Polyimidesmentioning
confidence: 82%
See 1 more Smart Citation
“…4 shows the results of the emission spectra for the 6FDA-mPDA, 6FDA-DAP, and 6FDA-DAR membranes. CTCs are typically formed between the nucleophilic fivemember rings and electrophilic six-member rings in polyimides [20,21,43]. The hydroxyl groups are likely to form hydrogen bonds, thereby tightening the polymer interchain structure to strengthen inter-chain CTCs, as evidenced by a previous study, which showed that hydroxyl moieties increased the intersegmental cohesive energy density (CED) in OH-functionalized polyimides [44].…”
Section: Physical Properties Of the Polyimidesmentioning
confidence: 82%
“…However, many polyimides have similar limitations in their practical use as cellulose acetate because of CO 2 -induced plasticization, which often results in unacceptable loss in CO 2 /CH 4 selectivity [16][17][18][19]. However, recent studies demonstrated that plasticization in polyimides can be mitigated to a large extend by various methods, such as: (i) Thermal annealing [20][21][22][23], (ii) chemical cross-linking [22,[24][25][26][27][28][29][30] and (iii) formation of charge transfer complexes [31].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the physical and chemical properties of glassy polymers are particularly influenced by thermal history [16][17][18][19][20][21][22][23][24][25] and physical aging [26][27][28][29][30][31][32], which can substantially change the material response to the external stresses and, what is of particular importance in the present discussion, can definitely affect its permeation properties.…”
Section: Introductionmentioning
confidence: 99%
“…Other works outline that different thermal treatments of the polymer matrix can influence significantly the transport rate of small size gases: the higher is the temperature of the pretreatment the lower is the final permeability, independently of the penetrant nature. The explanation proposed for this behavior is the reduction of the free volume available for the penetrant diffusion in the polymer matrix [17,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation